Fabulae moriendi : a ficcionalização da morte em quatro romances da literatura contemporanea portuguesa - Silva, Gabriela Farias da (2013)
This thesis aims at investigating the fictionalization of death in four contemporary Portuguese novels : Aparição, by Vergílio Ferreira; Lourenço é nome de jogral, by Fernanda Botelho; O triunfo da morte, by Augusto Abelaira; and As intermitências da morte de José Saramago. These novels were analyzed according to the concept of death proposed by the philosophical studies of Martin Heiddeger, Jean-Paul Sartre, Edgar Morin, Georges Bataille, Jean Baudrillard and Maurice Blanchot among others, as well as mythic, iconographic and historical aspects of the representation of death according to the studies of Phillipe Ariès and Johan Huizinga. Some theories of Narratology were also used in order to understand the complex relation and representation of death in Literature.